2022
DOI: 10.1136/bmjopen-2021-054137
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and level of depression among patients with chronic diseases, and associated factors during the COVID-19 lockdown: a cross-sectional study in rural Rwanda

Abstract: ObjectivesWe aimed to describe access to food and symptoms of depression among patients with chronic diseases or their caregivers, and assess associated factors during the COVID-19 lockdown in rural Rwanda.DesignA cross-sectional study.Setting and participantsA stratified random sampling technique was used to recruit 220 patients enrolled in the HIV, non-communicable diseases, mental health, paediatric development clinic and oncology programmes in three rural districts of Rwanda.Outcome measuresTelephone-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported that the pandemic had a significant negative impact on food insecurity and dietary habits among noncommunicable diseases patients [36,40,42,43,44]. Two cross-sectional studies conducted among patients with diabetes, revealed that more than half of participants had poor dietary practices [40,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COVID-19 on dietary habits among NCDs. Five studies reported that the pandemic had a significant negative impact on food insecurity and dietary habits among noncommunicable diseases patients [36,40,[42][43][44]. Two cross-sectional studies conducted among patients with diabetes, revealed that more than half of participants had poor dietary practices [40,42].…”
Section: Plos Onementioning
confidence: 99%
“…Food insecurity is defined as the state of lacking social, economic, and physical access to sufficient and nutritious food for the purpose of maintaining an active and healthy lifestyle (8). Two cross-section analysis showed that people with food insecurity was likely to be accompanied by worse psychological status (depression and suicide ideation) and higher risk of metabolism disorders (9)(10)(11). In addition, a study with 3,632 people (≥60 years old) enrolled indicated that the people probably prefer to have sarcopenia (low grip strength) compared to those with full food security (12).…”
mentioning
confidence: 99%